Current endoscopic approach to indeterminate biliary strictures - Victor, David W (Baishideng Publishing Group Co., Limited, 2012)
Biliary strictures are considered indeterminate when basic work-up, including transabdominal imaging and endoscopic retrograde cholangiopancreatography with routine cytologic brushing, are non-diagnostic. Indeterminate biliary strictures can easily be mischaracterized which may dramatically affect patient’s outcome. Early and accurate diagnosis of malignancy impacts not only a patient’s candidacy for surgery, but also potential timely targeted chemotherapies. A significant portion of patients with indeterminate biliary strictures have benign disease and accurate diagnosis is, thus, paramount to avoid unnecessary surgery. Current sampling strategies have suboptimal accuracy for the diagnosis of malignancy. Emerging data on other diagnostic modalities, such as ancillary cytology techniques, single operator cholangioscopy, and endoscopic ultrasonography-guided fine needle aspiration, revealed promising results with much improved sensitivity.